film

The film, featuring a 4-methyl-1-pentene copolymer with a tailored surface structure, enhances water repellency and transparency, addressing the limitations of conventional films in these areas.

JP7671171B2Active Publication Date: 2025-05-01MITSUI CHEMICALS INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021062268
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-05-01
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Conventional films containing 4-methyl-1-pentene copolymers have limitations in terms of water repellency, necessitating an improvement in this property.

Method used

A film comprising a 4-methyl-1-pentene copolymer with a specific concave-convex surface structure, characterized by convex portions with heights between 550 to 1,000 nm and spacings between 200 to 1,000 nm, as measured by atomic force microscopy.

Benefits of technology

The film achieves excellent water repellency while maintaining high transparency, making it suitable for various applications including food and medical packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671171000001
    Figure 0007671171000001
  • Figure 0007671171000002
    Figure 0007671171000002
Patent Text Reader

Abstract

To provide a film that contains a 4-methyl-1-pentene copolymer and has excellent water repellency.SOLUTION: A film contains a 4-methyl-1-pentene (co)polymer. The film has at least one surface that is in an uneven shape. The uneven shape includes projections that are 550-1000 nm high. The intervals between the projections are 200-1000 nm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to films, and more particularly to films comprising 4-methyl-1-pentene (co)polymers. [Background technology]

[0002] Films that combine transparency, stain resistance, and water repellency are widely used for a variety of purposes. For example, in food and medical applications, packaging films that are water repellent, have little adhesion to the contents, and are highly visible are required. In food applications, when moist foods adhere to the packaging film, problems occur in which the food is damaged or difficult to remove. In medical applications, it is required that the contents are visible without leaving any residual medicine. In addition, in applications that require light transparency, such as protective films for vinyl greenhouses and displays, not only transparency but also water repellency and stain resistance are required to protect the target.

[0003] Poly(4-methyl-1-pentene) is a resin that can meet these requirements because of its low surface tension and high transparency. Patent Document 1 discloses a resin composition for medical devices that contains a random copolymer of 4-methyl-1-pentene and a C4-C7 α-olefin and poly-4-methyl-1-pentene, and describes that the composition has excellent water repellency and that the contact angle with water of a square plate made from the composition was measured.

[0004] Patent Document 2 discloses a release film that is a laminate having a layer containing polymethylpentene in at least one outermost layer. On the other hand, Patent Documents 3 and 4 disclose a 4-methyl-1-pentene copolymer containing a 4-methyl-1-pentene copolymer component having a relatively large amount of comonomer and a 4-methyl-1-pentene copolymer component having a relatively small amount of comonomer, as well as a film made of such a 4-methyl-1-pentene copolymer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 62-246950 [Patent Document 2] JP 2006-212954 A [Patent Document 3] International Publication No. 2019 / 198694 [Patent Document 4] International Publication No. 2020 / 113638 Summary of the Invention [Problem to be solved by the invention]

[0006] However, conventional films containing 4-methyl-1-pentene copolymers have room for further improvement in terms of water repellency. An object of the present invention is to provide a film containing a 4-methyl-1-pentene copolymer, which has excellent water repellency. [Means for solving the problem]

[0007] The present invention relates to, for example, the following [1] to [7]. [1] A film comprising a 4-methyl-1-pentene (co)polymer, The film has an uneven shape on at least one surface thereof, and the height of the projections in the uneven shape is 550 to 1000 nm, and the interval between the projections is 200 to 1000 nm, as measured by the following method. Method for measuring height and spacing of convex portions: Observe the surface of the film with an atomic force microscope. From the obtained surface profile image, randomly select three measurement points, draw a straight line in the TD direction at each measurement point so that the ten convex portions are included, measure the height of each convex portion, and calculate the arithmetic average value. The height of each convex portion is the height from the deepest position of each measurement point. The arithmetic average value at the three measurement points is further arithmetically averaged, and the result is used as the height of the convex portions. Furthermore, from the obtained surface profile image, measure the distance between adjacent convex portions on the straight line at each of the above measurement points, and calculate the arithmetic average value. The arithmetic average value at the three measurement points is further arithmetically averaged, and the result is used as the spacing between the convex portions.

[0008] [2] The film of [1] above, wherein the 4-methyl-1-pentene (co)polymer is a 4-methyl-1-pentene copolymer (X) that satisfies the following requirements (Xa) to (Xb): Requirement (Xa): The amount (U1) of structural units derived from 4-methyl-1-pentene is 20.0 to 98.0 mol %, and the amount (U2) of structural units derived from an α-olefin having 2 to 20 carbon atoms other than 4-methyl-1-pentene is 80.0 to 2.0 mol % (however, the amount of all structural units is 100 mol %) (however, the amount of all structural units is 100 mol %). Requirement (Xb): Intrinsic viscosity [η] measured in decalin at 135°C X is 1.0-4.0 dL / g.

[0009] [3] The film of [2], wherein the 4-methyl-1-pentene copolymer (X) contains 90 to 5 parts by mass of a 4-methyl-1-pentene copolymer (A) satisfying the following requirements (Aa) to (Ac), and 10 to 95 parts by mass of a 4-methyl-1-pentene copolymer (B) satisfying the following requirements (Ba) to (Bc) and (B-a1) (wherein the total amount of the copolymers (A) and (B) is 100 parts by mass). Requirement (Aa): The amount of structural units (U3) derived from 4-methyl-1-pentene is 20.0 to 98.0 mol %, and the amount of structural units (U4) derived from an α-olefin having 2 to 20 carbon atoms other than 4-methyl-1-pentene is 80.0 to 2.0 mol % (the total of U3 and U4 is 100 mol %). Requirement (Ab): Intrinsic viscosity [η] measured in decalin at 135°C A is 1.5 to 8.0 dL / g. Requirement (Ac): The ratio (Mw / Mn) of the weight average molecular weight Mw to the number average molecular weight Mn, or the molecular weight distribution (Mw / Mn) which is the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn), measured by gel permeation chromatography (GPC) is 1.0 to 7.0. Requirement (Ba): The amount of structural units (U5) derived from 4-methyl-1-pentene is 80.0 to 99.9 mol %, and the amount of structural units (U6) derived from an α-olefin having 2 to 20 carbon atoms other than 4-methyl-1-pentene is 20.0 to 0.1 mol % (wherein the total of U5 and U6 is 100 mol %). Requirement (Bb): Intrinsic viscosity [η] measured in decalin at 135°C B is 0.5 to 5.0 dL / g. Requirement (Bc): The ratio (Mw / Mn) of the weight average molecular weight Mw to the number average molecular weight Mn, as measured by gel permeation chromatography (GPC), is 1.0 to 7.0. Requirement (B-a1): The ratio (U4 / U6) of the amount of the structural unit U4 (mol %) to the amount of the structural unit U6 (mol %) is greater than 1.0 and less than 50.0. [4] The film according to any one of [1] to [3] above, which is a stretched film.

[0010] [5] The film of any of the above [1] to [4], wherein the haze of the 4-methyl-1-pentene copolymer (X) is 5% or less when measured as a film having a thickness of 10 μm.

[0011] [6] The film according to any one of [1] to [5] above, which is for use in food.

[0012] [7] The film according to any one of [1] to [5] above for medical use. Effect of the Invention

[0013] The film of the present invention has excellent water repellency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will now be described in further detail. In the present invention, the term "(co)polymer" is a concept including both homopolymers and copolymers. In addition, in the present invention, a numerical range expressed using "~" means a range including the numerical values ​​before and after "~" as the lower and upper limits.

[0015] [film] The film according to the present invention is characterized in that it contains a 4-methyl-1-pentene (co)polymer and has a predetermined uneven shape on at least one surface.

[0016] The film according to the present invention contains a 4-methyl-1-pentene (co)polymer, i.e., a homopolymer of 4-methyl-1-pentene and / or a copolymer of 4-methyl-1-pentene and an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene).

[0017] Details of the α-olefin having 2 to 20 carbon atoms are as described in the description of requirement (Aa) below. Furthermore, the copolymer may further contain structural units derived from other polymerizable compounds as described in the description of requirement (Aa) below, within the scope of the invention.

[0018] [4-Methyl-1-pentene (co)polymer] The 4-methyl-1-pentene (co)polymer is preferably a 4-methyl-1-pentene copolymer (X) that satisfies the following requirements (Xa) and (Xb).

[0019] 《Requirements (Xa)》 The requirement (Xa) is that the amount (U1) of structural units derived from 4-methyl-1-pentene is 20.0 to 98.0 mol %, and the amount (U2) of structural units derived from an α-olefin having 2 to 20 carbon atoms other than 4-methyl-1-pentene is 80.0 to 2.0 mol %, provided that the amount of all structural units in the copolymer (X) is 100 mol %.

[0020] The content of U1 is preferably 51.0 to 98.0 mol %, more preferably 80.0 to 98.0 mol %, further preferably 90.0 to 97.5 mol %, and particularly preferably 95.0 to 97.0 mol %.

[0021] The content of U2 is preferably 49.0 to 2.0 mol %, more preferably 20.0 to 2.0 mol %, further preferably 10.0 to 2.5 mol %, and particularly preferably 5.0 to 3.0 mol %.

[0022] By satisfying the requirement (Xa), the film according to the present invention can ensure the stretchability. In the 4-methyl-1-pentene copolymer (X), the amount (U1) of structural units derived from the 4-methyl-1-pentene and the amount (U2) of structural units derived from an α-olefin having 2 to 20 carbon atoms other than 4-methyl-1-pentene can be calculated by the following formulas (1) and (2).

[0023] U1=(U3×W1+U5×W2) / (W1+W2)...Equation (1) U2=(U4×W1+U6×W2) / (W1+W2)...Equation (2) In the formula (1) and the formula (2), U3 is the amount (mol %) of structural units derived from 4-methyl-1-pentene in the 4-methyl-1-pentene copolymer (A) described below; U4 is the amount (mol %) of structural units derived from an α-olefin having 2 to 20 carbon atoms other than 4-methyl-1-pentene in the 4-methyl-1-pentene copolymer (A) described below; U5 is the amount (mol %) of structural units derived from 4-methyl-1-pentene in the 4-methyl-1-pentene copolymer (B) described below; U6 is the amount (mol %) of structural units derived from an α-olefin having 2 to 20 carbon atoms other than 4-methyl-1-pentene in the 4-methyl-1-pentene copolymer (B) described below; W1 is the content (parts by mass) of the 4-methyl-1-pentene copolymer (A) described below; W2 is the content (parts by mass) of the 4-methyl-1-pentene copolymer (B) described below. Represents.

[0024] 《Requirements (Xb)》 Requirement (Xb) is the intrinsic viscosity [η] measured in decalin at 135°C. X is 1.0 to 4.0 dL / g.

[0025] The intrinsic viscosity [η] X is preferably 2.0 to 4.0 dL / g. By satisfying the requirement (Xb), the film according to the present invention can ensure stretchability without impairing the film-forming stability.

[0026] The intrinsic viscosity [η] of the 4-methyl-1-pentene copolymer (X) measured in decalin at 135°C X can be calculated using the following formula (3). [η] X = ([η] A ×W1+[η] B ×W2) / (W1+W2)...Equation (3) In the formula (3), [η] A is the intrinsic viscosity [η] of the 4-methyl-1-pentene copolymer (A) described below, measured in decalin at 135°C. A ; [η] Bis the intrinsic viscosity [η] of the 4-methyl-1-pentene copolymer (B) described below, measured in decalin at 135°C. B ; W1 is the content (parts by mass) of the 4-methyl-1-pentene copolymer (A) described below; W2 is the content (parts by mass) of the 4-methyl-1-pentene copolymer (B) described below. Represents.

[0027] Other Requirements The 4-methyl-1-pentene copolymer (X) may further satisfy the following requirements.

[0028] Requirements (Xc): The requirement (Xc) is that the molecular weight distribution (Mw / Mn), which is the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn), measured by gel permeation chromatography (GPC) is 3.6 to 30.

[0029] The molecular weight distribution (Mw / Mn) is preferably 3.6 to 20, and more preferably 3.6 to 10. Each of the average molecular weights is a value calculated in terms of polystyrene measured by gel permeation chromatography (GPC) under the conditions employed in the examples described later. By satisfying the requirement (Xc), the film according to the present invention can suppress a decrease in transparency caused by the bleeding out of low molecular weight components.

[0030] (Preferred embodiment of 4-methyl-1-pentene copolymer (X)) From the viewpoint of facilitating the formation of a surface uneven structure, the 4-methyl-1-pentene copolymer (X) preferably contains 90 to 5 parts by mass of the 4-methyl-1-pentene copolymer (A) (hereinafter also simply referred to as "copolymer (A)") described below, and 10 to 95 parts by mass of the 4-methyl-1-pentene copolymer (B) (hereinafter also simply referred to as "copolymer (B)") described below (wherein the total amount of copolymer (A) and copolymer (B) is 100 parts by mass). In other words, the 4-methyl-1-pentene copolymer (X) is preferably a composition containing the 4-methyl-1-pentene copolymer (A) described below and the 4-methyl-1-pentene copolymer (B) described below.

[0031] The amount of the copolymer (A) is preferably 80 to 20 parts by mass, more preferably 70 to 30 parts by mass, and the amount of the copolymer (B) is preferably 20 to 80 parts by mass, more preferably 30 to 70 parts by mass.

[0032] <4-methyl-1-pentene copolymer (A)> The 4-methyl-1-pentene copolymer (A) is a 4-methyl-1-pentene copolymer that satisfies the following requirements (Aa), (Ab) and (Ac).

[0033] 《Requirement (Aa)》 Requirement (Aa) is that in the copolymer (A), the amount (U3) of structural units derived from 4-methyl-1-pentene is 20.0 to 98.0 mol %, and the amount (U4) of structural units derived from at least one selected from α-olefins having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 80.0 to 2.0 mol %.

[0034] U3 is preferably 20.0 to 97.0 mol%, more preferably 25.0 to 97.0 mol%, further preferably 50 to 97.0 mol%, particularly preferably 75 to 97.0 mol%, and most preferably 80 to 97.0 mol%. U4 is preferably 80.0 to 3.0 mol%, more preferably 75.0 to 3.0 mol%, further preferably 50 to 3.0 mol%, particularly preferably 25 to 3.0 mol%, and most preferably 20 to 3.0 mol%, provided that the sum of U3 and U4 is 100 mol%.

[0035] Examples of α-olefins having 2 to 20 carbon atoms include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene. In the present invention, ethylene is included in the α-olefins. Among these, from the viewpoints that the film of the present invention forms an uneven surface structure by stretching and can maintain high transparency even after stretching, α-olefins having 5 to 20 carbon atoms are preferred, α-olefins having 6 to 20 carbon atoms are more preferred, and α-olefins having 10 to 20 carbon atoms are even more preferred. Specifically, 1-hexene, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, and 1-octadecene are preferred, and 1-decene, 1-tetradecene, 1-hexadecene, and 1-octadecene are particularly preferred.

[0036] The copolymer (A) may have only one type of structural unit derived from an α-olefin having 2 to 20 carbon atoms, or may have two or more types. Copolymer (A) may further have structural units derived from other polymerizable compounds other than 4-methyl-1-pentene and α-olefins having 2 to 20 carbon atoms, provided that the object of the present invention is not impaired. Examples of other polymerizable compounds include vinyl compounds having a cyclic structure, such as styrene, vinylcyclopentene, vinylcyclohexane, and vinylnorbornane; vinyl esters, such as vinyl acetate; unsaturated organic acids or derivatives thereof, such as maleic anhydride; conjugated dienes, such as butadiene, isoprene, pentadiene, and 2,3-dimethylbutadiene; 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, 7-methyl-1,6-octadiene, Examples of non-conjugated polyenes include dicyclopentadiene, cyclohexadiene, dicyclooctadiene, methylenenorbornene, 5-vinylnorbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, 6-chloromethyl-5-isopropenyl-2-norbornene, 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, and 2-propenyl-2,2-norbornadiene.

[0037] In the copolymer (A), the content of structural units derived from other polymerizable compounds is usually 10 mol % or less, preferably 5 mol % or less, and more preferably 3 mol % or less, based on 100 mol % of all structural units constituting the copolymer (A).

[0038] When copolymer (A) contains two or more copolymers, the amount (U3) of structural units derived from 4-methyl-1-pentene and the amount (U4) of structural units derived from an α-olefin having 2 to 20 carbon atoms in copolymer (A) can be the average value of each copolymer taking into consideration the mass ratio. It is preferable that each copolymer has the amount of structural units derived from 4-methyl-1-pentene and the amount of structural units derived from an α-olefin having 2 to 20 carbon atoms within the numerical range of U3 and U4.

[0039] 《Requirements (Ab)》 The requirement (Ab) is the intrinsic viscosity [η] measured in decalin at 135°C. A is 1.5 to 8.0 dL / g.

[0040] The above [η] A is preferably 2.0 to 7.5 dL / g, more preferably 2.2 to 7.0 dL / g, further preferably 2.4 to 6.0 dL / g, and particularly preferably 2.6 to 5.0 dL / g.

[0041] [η] A The copolymer (A) having a molecular weight of 1.0 or less in the above range exhibits good fluidity during preparation and molding of the resin composition, and is considered to contribute to improved stretchability when combined with the 4-methyl-1-pentene copolymer (B).

[0042] When the copolymer (A) contains two or more types of copolymers, the intrinsic viscosity [η] A can be the average value of [η] of each copolymer taking into account the mass ratio. A It is preferable that [η] is in the numerical range of

[0043] 《Requirements (Ac)》 Requirement (Ac) is that the molecular weight distribution (Mw / Mn), which is the ratio of weight average molecular weight Mw to number average molecular weight Mn (Mw / Mn) or the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn), is 1.0 to 7.0, as measured by gel permeation chromatography (GPC).

[0044] The molecular weight distribution (Mw / Mn) is preferably 1.0 to 6.5, and more preferably 1.2 to 6.0. Each of the average molecular weights is a value calculated in terms of polystyrene, measured by gel permeation chromatography (GPC) under the conditions employed in the examples described later.

[0045] (Method for producing 4-methyl-1-pentene copolymer (A)) The 4-methyl-1-pentene copolymer (A) can be produced by a conventional method, for example, the methods described in WO 2019 / 198694, WO 2020 / 116368, and WO 2006 / 054613.

[0046] <4-methyl-1-pentene copolymer (B)> The 4-methyl-1-pentene copolymer (B) is a 4-methyl-1-pentene copolymer that satisfies the following requirements (Ba), (Bb), (Bc) and (B-a1).

[0047] Requirements (Ba) The requirement (Ba) is that in the copolymer (B), the amount (U5) of structural units derived from 4-methyl-1-pentene is 80.0 to 99.9 mol %, and the amount (U6) of structural units derived from at least one selected from α-olefins having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 20.0 to 0.1 mol %.

[0048] U5 is preferably 85.0 to 99.9 mol %, more preferably 90.0 to 99.9 mol %. U6 is preferably 15.0 to 0.1 mol %, more preferably 10.0 to 0.1 mol %, provided that the total of U5 and U6 is 100 mol %.

[0049] Examples of α-olefins having 2 to 20 carbon atoms include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene. Among these, from the viewpoint that the film of the present invention has a surface uneven structure formed by stretching and can maintain high transparency even after stretching, α-olefins having 5 to 20 carbon atoms are preferred, and α-olefins having 10 to 20 carbon atoms are more preferred. Specifically, 1-hexene, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, and 1-octadecene are preferred, and 1-decene, 1-tetradecene, 1-hexadecene, and 1-octadecene are particularly preferred.

[0050] The copolymer (B) may have only one type of structural unit derived from an α-olefin having 2 to 20 carbon atoms, or may have two or more types. The copolymer (B) may further contain structural units derived from other polymerizable compounds mentioned in the description of requirement (Aa) within the scope of the invention.

[0051] In the copolymer (B), the content of structural units derived from other polymerizable compounds is usually 10 mol % or less, preferably 5 mol % or less, and more preferably 3 mol % or less, based on 100 mol % of all structural units constituting the copolymer (B).

[0052] When copolymer (B) contains two or more copolymers, the amount (U5) of structural units derived from 4-methyl-1-pentene and the amount (U6) of structural units derived from an α-olefin having 2 to 20 carbon atoms in copolymer (B) can be the average value of each copolymer taking into consideration the mass ratio. It is preferable that each copolymer has the amount of structural units derived from 4-methyl-1-pentene and the amount of structural units derived from an α-olefin having 2 to 20 carbon atoms within the numerical range of U5 and U6.

[0053] 《Requirements (Bb)》 Requirement (Bb) is the intrinsic viscosity [η] measured in decalin at 135°C B is 0.5 to 5.0 dL / g. B is preferably 0.5 to 4.5 dL / g, and more preferably 0.5 to 4.0 dL / g.

[0054] [η] B The copolymer (B) having a viscosity in the above range exhibits good fluidity during preparation and molding of the resin composition, and is considered to contribute to improved stretchability when combined with the 4-methyl-1-pentene copolymer (A).

[0055] When the copolymer (B) contains two or more types of copolymers, the intrinsic viscosity [η] Bcan be the average value of [η] of each copolymer taking into account the mass ratio. B It is preferable that [η] is in the numerical range of

[0056] 《Requirements (Bc)》 Requirement (Bc) is that the molecular weight distribution (Mw / Mn), which is the ratio of weight average molecular weight Mw to number average molecular weight Mn (Mw / Mn) or the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn), is 1.0 to 7.0, as measured by gel permeation chromatography (GPC).

[0057] The molecular weight distribution (Mw / Mn) is preferably 2.0 to 7.0, and more preferably 3.0 to 6.5. Each of the average molecular weights is a value calculated in terms of polystyrene, measured by gel permeation chromatography (GPC) under the conditions employed in the examples described later. By satisfying the requirement (Bc), the film according to the present invention can suppress the decrease in transparency caused by the bleed-out of low molecular weight components and can ensure a sufficient stretch ratio.

[0058] 《Requirements (B-a1)》 Requirement (B-a1) is that the ratio (U4 / U6) of the amount of the structural units U4 (mol %) (the amount of structural units derived from an α-olefin having 2 to 20 carbon atoms in copolymer (A)) to the amount of the structural units U6 (mol %) (the amount of structural units derived from an α-olefin having 2 to 20 carbon atoms in copolymer (B)) is greater than 1.0 and less than 50.0.

[0059] The ratio (U4 / U6) is preferably 1.0 to 40.0, and more preferably 2.0 to 40.0. The requirement (B-a1) means that the copolymer (B) has a higher content of structural units derived from the α-olefin that is a comonomer for 4-methyl-1-pentene than the copolymer (A).

[0060] When the requirement (B-a1) is satisfied, the film according to the present invention can form an uneven structure on the surface when stretched. The 4-methyl-1-pentene copolymer (B) preferably satisfies the following requirement (Bd).

[0061] 《Requirements (Bd)》 The requirement (Bd) is that when the copolymer (B) is measured by a cross fractionation chromatograph (CFC) using an infrared spectrophotometer as a detection section, at least one peak of the amount of an eluted component is present in the range of 100 to 140°C.

[0062] The peak of the amount of the eluted components is preferably present in the range of 100 to 135° C. The position of the peak of the amount of the eluted components is determined from the position of the peak top. In one embodiment, the copolymer (B) preferably has no peak in the amount of eluted components in the range of 0°C or higher and lower than 100°C.

[0063] By satisfying the requirement (Bd), the film according to the present invention can suppress a decrease in transparency caused by the bleeding out of low molecular weight components. The content of components eluted at 135° C. or higher in the total amount of components eluted at 0 to 145° C. of the copolymer (B) is preferably 30% by mass or less, more preferably 25% by mass or less, and further preferably 20% by mass or less. The copolymer (B) satisfying this requirement is preferred from the viewpoint of uniform stretchability.

[0064] (Method for producing 4-methyl-1-pentene copolymer (B)) The 4-methyl-1-pentene copolymer (B) can be produced by a conventional method, for example, the method described in WO 2019 / 198694, WO 2020 / 116368, or WO 2006 / 054613.

[0065] (Method for producing 4-methyl-1-pentene copolymer (X) containing copolymer (A) and copolymer (B)) The 4-methyl-1-pentene copolymer (X) containing the copolymer (A) and the copolymer (B) can be obtained by mixing the copolymer (A) and the copolymer (B) with additives described below as necessary. The mixture of the copolymer (A) and the copolymer (B) may be prepared by the multi-stage polymerization method described in WO 2019 / 198694, WO 2020 / 116368, etc.

[0066] The components can be mixed by various known methods, for example, by mixing the components using an apparatus such as a plastomill, a Henschel mixer, a V-blender, a ribbon blender, a tumbler, a blender, or a kneader-ruder; or by further melt-kneading the mixture obtained after the above mixing using an apparatus such as a single-screw extruder, a twin-screw extruder, a kneader, or a Banbury mixer, and then granulating or pulverizing the resulting melt-kneaded product.

[0067] <Additives> The film according to the present invention may contain additives together with the 4-methyl-1-pentene (co)polymer within the range that does not impair the effects of the present invention, or may not contain any additives.

[0068] Examples of additives include secondary antioxidants, heat stabilizers, weather stabilizers, antistatic agents, slip agents, antiblocking agents, antifogging agents, lubricants, dyes, pigments, natural oils, synthetic oils, waxes, fillers, hydrochloric acid absorbents, and polymers other than 4-methyl-1-pentene (co)polymers.

[0069] <Uneven surface shape> The film according to the present invention has an uneven shape on at least one surface, and the height of the projections in the uneven shape is 550 to 1000 nm and the interval between the projections is 200 to 1000 nm, as measured by the following method.

[0070] The film according to the present invention preferably has the above-mentioned uneven shape on both sides. The height of the convex portions is preferably 550 to 950 nm, more preferably 550 to 900 nm, and further preferably 550 to 800 μm. The interval between the convex portions is 200 to 1000 nm. Since the height of the protrusions and the interval between the protrusions are within the above ranges, the film according to the present invention exhibits high water repellency and can further increase transparency.

[0071] (Method for measuring unevenness of film surface) Using a scanning probe microscope of atomic force microscope (e.g., AFM-5300E manufactured by Hitachi High-Tech Science Corporation) and a silicon cantilever, three randomly selected locations within an area of ​​20 μm x 20 μm on the film surface are observed at room temperature (23°C).

[0072] From the obtained surface shape image, three measurement points are randomly selected, and a straight line is drawn in the TD direction at each measurement point so that the 10 convex parts are included. The height of each convex part is measured, and the arithmetic average value is calculated. Note that a convex part refers to an area that is higher than the midpoint between the deepest position (i.e., the lowest position) and the highest position within each measurement point. Therefore, it is possible that unevenness exists within one convex part. The height of each convex part is the height from the deepest position of each measurement point. The arithmetic average values ​​at the three measurement points are further arithmetically averaged, and the result is used as the height of the convex part.

[0073] In addition, the distance between adjacent convex portions on the line (the distance between the highest points of the convex portions on the surface profile image) is measured at each of the measurement points, and the arithmetic mean value is calculated. The arithmetic mean values ​​at the three measurement points are further arithmetically averaged, and the result is used as the distance between the convex portions.

[0074] The thickness of the film of the present invention is, for example, 8 to 70 μm, and preferably 8 to 50 μm. The film of the present invention has high transparency, and for example, the haze of a 10 μm-thick film measured under the conditions employed in the examples described below is preferably 5% or less, more preferably 4% or less.

[0075] [Film manufacturing method] Examples of methods for producing the film according to the present invention include: forming the mixture containing the 4-methyl-1-pentene (co)polymer, and optionally the additives, into an unstretched film; and A step of stretching the unstretched film to form the uneven shape on the film surface. and preferably, forming a mixture containing the 4-methyl-1-pentene copolymer (X) and, optionally, the additives, into an unstretched film; and A step of stretching the unstretched film under conditions described below to form the uneven shape on the film surface. The manufacturing method includes the steps of:

[0076] As the 4-methyl-1-pentene copolymer (X), a 4-methyl-1-pentene copolymer (X) containing the above-mentioned copolymer (A) and copolymer (B) is preferably used.

[0077] As a method for forming the mixture containing the 4-methyl-1-pentene (co)polymer and, optionally, the additives into an unstretched film, a conventionally known method can be used. The unstretched film can be stretched by any conventional method, but the following stretching conditions are preferably applied.

[0078] (Stretching conditions) Stretching ratio: 2-4x on MD and 1-4x on TD Preferably, 2 to 3.5 times in MD and 1 to 3.5 times in TD. Unstretched Film Thickness: 100~300μm Preheat temperature: 100~200℃ Preheat time: 1-2 minutes Stretching temperature: 100~200℃ Stretching speed: 50~150% / sec Annealing conditions: 130~210℃, 0.5~2 minutes Methods for stretching the film include, for example, uniaxial stretching, biaxial sequential stretching, and biaxial simultaneous stretching. Among these, uniaxial stretching and biaxial sequential stretching are preferred because they give stretched films with high protrusions.

[0079] [Film Uses] The film according to the present invention has high water repellency and high transparency, and therefore can be preferably used as a film for food products and a film for medical use.

[0080] The film, for example, Food films such as commercial wrap films, household wrap films, processed fish packaging materials, vegetable packaging materials, fruit packaging materials, fermented food packaging materials, confectionery packaging materials, oxygen absorbent packaging materials, retort food packaging materials, freshness preservation films, bulb packaging materials, seed packaging materials, vegetable and mushroom cultivation films, etc.; Medical films such as pharmaceutical packaging, cell examination films, and packaging for high-temperature treatment such as boiling and high-pressure steam sterilization; It is used as.

[0081] Examples of uses for the above film that can be further processed include: Retort food containers, heat-resistant vacuum-formed containers, prepared food containers, lids for prepared food, baking cartons, tableware, condiment containers, kitchenware, retort containers, freezer storage containers, retort pouches, microwave heat-resistant containers, frozen food containers, ice cream cups, cups, baby bottles, beverage bottles and other food containers; Blood transfusion sets, medical bottles, medical containers, medical tubes, infusion tubes, connectors and packings, hollow medical bottles, medical bags, infusion bags, blood storage bags, infusion bottles, medicine containers, detergent containers, fabric softener containers, bleach containers, vials, plastic syringes, prefilled syringes, cell culture bags, cell culture containers, medical gaskets, medical caps, medicine stoppers, gaskets, and other medical instruments; Physics and chemistry laboratory equipment such as beakers, petri dishes, flasks, animal cages, storage containers, etc.; Various medical test kits such as PCR plates, PCR tubes, foil seals for PCR plates, buffer containers, marker containers, etc. Examples include: EXAMPLES

[0082] [Measurement or evaluation method] The raw materials used and the films produced in the examples were measured and evaluated by the following methods.

[0083] [Copolymer] <Method for measuring intrinsic viscosity [η]> Intrinsic viscosity [η] of copolymer (Intrinsic viscosity [η] X , [η] A or [η] B ) was measured using an Ubbelohde viscometer in decalin solvent at 135°C.

[0084] Specifically, about 20 mg of powdered copolymer was dissolved in 25 ml of decalin, and the specific viscosity ηsp was measured using an Ubbelohde viscometer in an oil bath at 135°C. After diluting this decalin solution by adding 5 ml of decalin, the specific viscosity ηsp was measured in the same manner as above. This dilution procedure was repeated two more times, and the value of ηsp / C when the concentration (C) was extrapolated to 0 was taken as the limiting viscosity [η] (unit: dl / g) (see the formula below). [η]=lim(ηsp / C) (C→0)

[0085] <Method for measuring comonomer content> The content of the structural units derived from the comonomer in the 4-methyl-1-pentene copolymer (comonomer content) was measured using the following apparatus and conditions: 13 Calculated from C-NMR spectrum. Measurement equipment: Bruker Biospin AVANCEIIIcryo-500 nuclear magnetic resonance spectrometer Solvent: o-dichlorobenzene / benzene-d6 (4 / 1 v / v) mixed solvent Sample concentration: 55mg / 0.6mL Measured temperature; 120 °C Observed nucleus: 13 C (125 MHz) Sequence: Single pulse proton broadband decoupling Pulse width: 5.0 μs (45° pulse) Repetition time: 5.5 s Number of integrations: 64 times Chemical shift reference: Benzene-d6 (128 ppm) Using the integrated value of the main chain methine signal, the content of the structural unit derived from the comonomer was calculated by the following formula. Content of the structural unit derived from the comonomer (%) = [P / (P + M)] × 100 〔P represents the total peak area of the comonomer main chain methine signal, and M represents the total peak area of the 4-methyl-1-pentene main chain methine signal.〕

[0086] <Mw / Mn measurement method> The weight average molecular weight (Mw) and number average molecular weight (Mn) were measured by GPC. The GPC measurement was carried out under the following conditions. Also, the weight average molecular weight (Mw) and number average molecular weight (Mn) were determined based on the following conversion method using a commercially available monodisperse standard polystyrene to create a calibration curve.

[0087] (Measurement conditions) Apparatus: Gel permeation chromatograph HLC-8321 GPC / HT type (manufactured by Tosoh Corporation) Organic solvent: o-dichlorobenzene Columns: Two TSKgel GMH6-HT columns and two TSKgel GMH6-HTL columns (both manufactured by Tosoh Corporation) Flow rate: 1.0 ml / min Sample: 0.15 mg / mL o-dichlorobenzene solution Temperature: 140 °C Molecular weight conversion: PS conversion / Universal calibration method

[0088] The coefficients of the Mark-Houwink viscosity equation were used for the calculation of the general calibration. The Mark-Houwink coefficients of PS were the values ​​listed in the literature (J. Polym. Sci., Part A-2, 8, 1803 (1970)).

[0089] 〔film〕 <How to measure haze> The film used for measurement was a stretched film having a thickness of 10 μm, prepared by the method described in the Examples and the like.

[0090] The film was cut into a 10 cm square to prepare a measurement sample, and the haze was measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory Co., Ltd.) at room temperature (23° C.) using a D65 light source in accordance with JIS K7136.

[0091] <Water contact angle> The film used for measurement was a stretched film prepared by the method described in the Examples (a film with a thickness of 200 μm was prepared and then stretched at an arbitrary magnification). A contact angle was measured in an atmosphere of 23° C. and 50% RH using a contact angle meter (CA-XE model manufactured by Kyowa Interface Science Co., Ltd.) in accordance with JIS R3257, except that the substrate glass was changed to the film. The film was cut into a 10 cm square, and the arithmetic average value of contact angles at five points within the same sample was taken as the water contact angle.

[0092] <Surface observation method> The film used for measurement was a stretched film prepared by the method described in the Examples (a film having a thickness of 200 μm was prepared and then stretched at an arbitrary ratio).

[0093] The film was cut into 1 cm squares and platinum-coated. Ten randomly selected locations on the surface were then observed at 3000x magnification using an SEM (scanning electron microscope, JEOL Ltd. JSM-6380). The surface structure was described as follows: Streaky: All 10 locations have streaky irregularities on the surface extending in the MD direction. Crater-like: All 10 locations have crater-like irregularities on the surface. No structure: There are no streaks or crater-like irregularities on the surface in any of the 10 locations.

[0094] Surface shape measurement method: A measurement sample of 5 cm square was cut from near the center of the stretched film. Using an atomic force microscope (AFM5300E, Hitachi High-Tech Science Corp.), the uneven structure was observed at three randomly selected locations within a 20 μm × 20 μm area on the film surface used for SEM surface observation. Using a silicon cantilever (Olympus Corp.), the surface shape image was observed at room temperature (23°C).

[0095] Three measurement points were randomly selected from the obtained surface shape image, and a straight line was drawn in the TD direction at each measurement point so that 10 convex parts were included. The height of each convex part was measured and the arithmetic mean value was calculated. Note that a convex part refers to an area that is higher than the midpoint between the deepest and highest points in each measurement point. Therefore, it is possible that unevenness exists within one convex part. The height of each convex part was taken as the height from the deepest point of each measurement point. The arithmetic mean values ​​of the three measurement points were further arithmetically averaged and the result was adopted as the height of the convex part.

[0096] In addition, the distance between adjacent convex portions on the line (the distance between the highest points of the convex portions on the surface profile image) was measured at each of the measurement points, and the arithmetic mean value was calculated. The arithmetic mean values ​​at the three measurement points were further arithmetically averaged, and the result was used as the distance between the convex portions.

[0097] [Synthesis Example 1] [Preparation of prepolymerized catalyst component] According to Synthesis Example 1 of WO 2019 / 198694, 100 mL of a decane slurry (i.e., a decane slurry of a prepolymerized catalyst component) was obtained.

[0098] [Polymerization Example 1] [Production of Copolymer (A-1)] At room temperature (25°C) and under a nitrogen stream, 425mL of purified decane and 0.5mL (0.4mmol in terms of aluminum atoms) of triethylaluminum solution (0.8mmol / mL in terms of aluminum atoms) were charged into a SUS polymerization vessel equipped with a stirrer having an internal volume of 1L. Next, 0.0016mmol in terms of zirconium atoms of the decane slurry of the prepolymerized catalyst component prepared in Synthesis Example 1 was added, and the temperature was raised to 40°C. After reaching 40°C, 35NmL of hydrogen was charged, and then 180mL of 4-methyl-1-pentene (4MP-1) and 33mL of a mixture of 43mol% 1-hexadecene and 57mol% 1-octadecene were continuously charged into the polymerization vessel at a constant rate over 80 minutes. The start of this charging was regarded as the start of polymerization, and the temperature was maintained at 45°C for 3 hours. Then, the temperature was lowered to room temperature, the pressure was released, and the polymerization liquid (slurry) containing the white solid was immediately filtered to obtain a solid substance, which was then dried under reduced pressure at 80°C for 8 hours to obtain a 4-methyl-1-pentene copolymer (A-1).

[0099] [Polymerization Example 2] [Production of Copolymer (A-2)] A 4-methyl-1-pentene copolymer (A-2) was obtained by the same procedure as in Polymerization Example 1, except that the amount of 4-methyl-1-pentene charged was changed to 70 mL, the amount of the mixture charged was changed to 14 mL, and the amount of hydrogen charged was changed to 4.4 NmL.

[0100] [Polymerization Example 3] [Production of Copolymer (B-1)] A 4-methyl-1-pentene copolymer (B-1) was obtained by the same procedure as in Polymerization Example 1, except that the amount of 4-methyl-1-pentene charged was changed to 170 mL, the amount of the mixture charged was changed to 30 mL, and the amount of hydrogen charged was changed to 33 NmL.

[0101] [Polymerization Example 4] [Production of Copolymer (B-2)] A 4-methyl-1-pentene copolymer (B-2) was obtained by the same procedure as in Polymerization Example 1, except that the amount of 4-methyl-1-pentene charged was changed to 115 mL, the amount of the mixture charged was changed to 2 mL, and the amount of hydrogen charged was changed to 26 NmL. The physical properties of the obtained polymer are shown in Table 1.

[0102] [Table 1]

[0103] [Film Production] [Example 1] <Mixing and film-forming process> 65 parts by mass of copolymer (A-1) and 35 parts by mass of copolymer (B-1) were dry blended, and 0.1 parts by mass of tri(2,4-di-t-butylphenyl)phosphate as a secondary antioxidant and 0.1 parts by mass of n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate as a heat stabilizer were blended with respect to 100 parts by mass of the resulting blend. The resulting blend was fed into a 20 mmφ single-screw extruder (single-screw sheet forming machine, manufactured by Tanaka Iron Works Co., Ltd.) equipped with a T-die with a lip width of 240 mm, and film-formed under conditions of a die temperature of 270°C and a roll temperature of 70°C. During film formation, a number of unstretched films with different thicknesses were produced, specifically, a 200 μm thick unstretched film and an unstretched film for haze measurement whose thickness was adjusted to 10 μm after stretching were obtained.

[0104] <Stretching process> The unstretched film was cut into 12 cm squares and uniaxially stretched using a batch-type biaxial stretching machine (Bruckner, KARO IV) to obtain a stretched film. The stretching conditions were a preheating temperature of 160°C, a preheating time of 1 minute, a stretching temperature of 160°C, a stretching speed of 104% / sec, and a stretch ratio of 3 times in the MD direction. The annealing conditions were 200°C and 1 minute. The physical properties of the produced stretched film were evaluated by the above-mentioned methods.

[0105] [Example 2] The unstretched film was stretched 3 times in the MD direction, and then further stretched in the TD direction at a stretching temperature of 160°C, a stretching speed of 104% / sec, and a stretch ratio of 3 times. A stretched film having a thickness of 10 μm was produced in the same manner as in Example 1, and its physical properties were evaluated.

[0106] [Example 3] A stretched film was produced in the same manner as in Example 1 except that the unstretched film was simultaneously biaxially stretched with a preheating temperature of 160°C, a preheating time of 1 minute, a stretching temperature of 160°C, a stretching speed of 104% / sec in the MD direction, a stretching ratio of 3 times in the MD direction, and a stretching speed of 104% / sec in the TD direction, a stretching ratio of 3 times in the TD direction, and the like. The physical properties of the stretched film were evaluated.

[0107] [Example 4] A stretched film was produced in the same manner as in Example 1, except that the dry blend of copolymer (A-1) and copolymer (B-1) was changed to a dry blend of 61 parts by mass of copolymer (A-2) and 39 parts by mass of copolymer (B-2), and the physical properties thereof were evaluated.

[0108] [Example 5] A stretched film was produced in the same manner as in Example 4, except that the film stretched 3 times in the MD direction was further stretched 3 times in the TD direction at a stretching temperature of 160°C and a stretching speed of 104% / sec. The physical properties of the stretched film were evaluated.

[0109] [Comparative Example 1] A film (raw film) was produced in the same manner as in Example 1 except that the stretching step was not carried out, and its physical properties were evaluated.

[0110] [Comparative Example 2] A stretched film was produced in the same manner as in Example 2, except that the stretching ratio in the TD direction was changed to 5 times, and the physical properties of the film were evaluated.

[0111] [Comparative Example 3] A stretched film was produced in the same manner as in Example 5, except that the stretching ratio in the TD direction was changed to 5 times, and the physical properties of the film were evaluated.

[0112] [Comparative Example 4] A stretched film was produced in the same manner as in Example 1, except that the stretching ratio in the MD direction was changed to 5 times, and the physical properties of the film were evaluated.

[0113] [Comparative Example 5] A stretched film was produced in the same manner as in Example 4, except that the stretching ratio in the MD direction was changed to 5 times, and the physical properties of the film were evaluated. The evaluation results of the physical properties of each film are shown in Table 2.

[0114] [Table 2]

Claims

1. A film comprising a 4-methyl-1-pentene (co)polymer, The film has an uneven shape on at least one surface thereof, and the height of the protrusions in the uneven shape is 550 to 1000 nm, and the interval between the protrusions is 200 to 1000 nm, as measured by the following method. Measurement method of height and interval of convex parts: Observe the surface of the film with an atomic force microscope. From the obtained surface shape image, randomly select three measurement points, draw a straight line in the TD direction at the measurement points so that 10 convex parts are included, measure the height of each convex part, and obtain the arithmetic average value. The height of each convex part is the height from the deepest position of each measurement point. The arithmetic average value at the three measurement points is further arithmetically averaged, and the result is adopted as the height of the convex part. Furthermore, from the obtained surface shape image, the distance between adjacent convex parts on the straight line at each of the above measurement points is measured, and the arithmetic average value is obtained. The arithmetic average value at the three measurement points is further arithmetically averaged, and the result is adopted as the interval between the convex parts.

2. 2. The film according to claim 1, wherein the 4-methyl-1-pentene (co)polymer is a 4-methyl-1-pentene copolymer (X) that satisfies the following requirements (Xa) and (Xb): Requirement (X-a): The amount (U1) of structural units derived from 4-methyl-1-pentene is 20.0 to 98.0 mol %, and the amount (U2) of structural units derived from an α-olefin having 2 to 20 carbon atoms other than 4-methyl-1-pentene is 80.0 to 2.0 mol % (with the total amount of structural units being 100 mol %) (with the total amount of structural units being 100 mol %). Requirement (X-b): Intrinsic viscosity [η] measured in decalin at 135 ° C. X is 1.0 to 4.0 dL / g.

3. The film according to claim 2, wherein the 4-methyl-1-pentene copolymer (X) contains 90 to 5 parts by mass of a 4-methyl-1-pentene copolymer (A) satisfying the following requirements (A-a) to (A-c), and 10 to 95 parts by mass of a 4-methyl-1-pentene copolymer (B) satisfying the following requirements (B-a) to (B-c) and (B-a1) (wherein the total amount of the copolymer (A) and the copolymer (B) is 100 parts by mass). Requirement (A-a): The amount of structural units (U3) derived from 4-methyl-1-pentene is 20.0 to 98.0 mol %, and the amount of structural units (U4) derived from an α-olefin having 2 to 20 carbon atoms other than 4-methyl-1-pentene is 80.0 to 2.0 mol % (with the sum of U3 and U4 being 100 mol %). Requirement (A-b): Intrinsic viscosity [η] measured in decalin at 135 ° C. A is 1.5 to 8.0 dL / g. Requirement (Ac): The ratio (Mw / Mn) of the weight average molecular weight Mw to the number average molecular weight Mn, or the molecular weight distribution (Mw / Mn) which is the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn), measured by gel permeation chromatography (GPC) is 1.0 to 7.

0. Requirement (Ba): The amount of structural units (U5) derived from 4-methyl-1-pentene is 80.0 to 99.9 mol %, and the amount of structural units (U6) derived from an α-olefin having 2 to 20 carbon atoms other than 4-methyl-1-pentene is 20.0 to 0.1 mol % (with the sum of U5 and U6 being 100 mol %). Requirement (B-b): Intrinsic viscosity [η] measured in decalin at 135 ° C. B is 0.5 to 5.0 dL / g. Requirement (Bc): The ratio of weight average molecular weight Mw to number average molecular weight Mn (Mw / Mn), measured by gel permeation chromatography (GPC), is from 1.0 to 7.

0. Requirement (B-a1): The ratio (U4 / U6) of the amount of the structural unit U4 (mol %) to the amount of the structural unit U6 (mol %) is greater than 1.0 and less than 50.

0.

4. The film according to any one of claims 1 to 3, which is a stretched film.

5. The film according to any one of claims 1 to 4, wherein the 4-methyl-1-pentene copolymer (X) has a haze of 5% or less when measured as a film having a thickness of 10 µm.

6. The film according to any one of claims 1 to 5, for use in food products.

7. The film according to any one of claims 1 to 5 for medical use.

Citation Information

Patent Citations

  • Resin composition for medical appliance

    JP1987246950A

  • Wrap film for household purpose

    JP2002012257A

  • Manufacturing process for resin film

    JP2005088600A

  • Mold release film

    JP2006212954A

  • Film for capacitor, metallized film and film capacitor

    JP2014011181A